2011
DOI: 10.1128/jcm.00508-11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Two New Molecular Methods for Identification of Candida parapsilosis Sensu Lato Species

Abstract: Candida parapsilosis sensu stricto, C. orthopsilosis, and C. metapsilosis replaced C. parapsilosis groups I, II, and III in 2005. Since then, an increased interest in studying their epidemiology has arisen based on the observed differences in antifungal susceptibilities and virulence the three species. A strict differentiation of these species cannot be achieved by phenotypic methods. We evaluate two new molecular methodologies to differentiate among these species by the use of a collection of 293 bloodstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…Although C. parapsilosis sensu stricto is responsible for the vast majority of human diseases associated with the three Candida species of the "psilosis" group, it is known that C. orthopsilosis and C. metapsilosis show antifungal susceptibility profiles different from that of C. parapsilosis that could affect therapeutic choices (25). To date, no commercial systems are currently available for this purpose (26,27), but the low rates of antifungal resistance in fungemias caused by C. orthopsilosis and C. metapsilosis strains (9, 12) may counterbalance this lack. Of note, no isolation of Candida nivariensis-two isolates were studied here-and Candida bracarensis was reported in those survey studies (9,12), in spite of the clinical, but moderate, interest elicited with respect to these C. glabrata-related species due to the propensity of some isolates to exhibit antifungal resistance (28).…”
mentioning
confidence: 99%
“…Although C. parapsilosis sensu stricto is responsible for the vast majority of human diseases associated with the three Candida species of the "psilosis" group, it is known that C. orthopsilosis and C. metapsilosis show antifungal susceptibility profiles different from that of C. parapsilosis that could affect therapeutic choices (25). To date, no commercial systems are currently available for this purpose (26,27), but the low rates of antifungal resistance in fungemias caused by C. orthopsilosis and C. metapsilosis strains (9, 12) may counterbalance this lack. Of note, no isolation of Candida nivariensis-two isolates were studied here-and Candida bracarensis was reported in those survey studies (9,12), in spite of the clinical, but moderate, interest elicited with respect to these C. glabrata-related species due to the propensity of some isolates to exhibit antifungal resistance (28).…”
mentioning
confidence: 99%
“…As current methods for yeast identification are based on phenotypic features, they can neither differentiate among the three closely related C. parapsilosis sensu lato species nor reliably discriminate isolates below the species level within the C. parapsilosis sensu stricto group. To ensure optimal therapeutic options and study nosocomial cross-transmission, molecular identification of C. parapsilosis outbreak isolates at the species level is therefore of utmost importance (10).…”
mentioning
confidence: 99%
“…This method provides a rapid identification; however, the assay may exhibit low reproducibility because it is possible to observe variations in the melting curve when different thermocyclers are used (17). Garcia-Effron et al (11) proposed a new real-time PCR assay that can differentiate these 3 species using the molecular beacon technology and the ITS region as the target. This assay was highly specific, exhibited good reproducibility, and showed that the C. parapsilosis species complex can be identified quickly, thus demonstrating its suitability for clinical applications (11).…”
Section: Discussionmentioning
confidence: 99%
“…These authors have shown that this method identifies the 3 species within the C. parapsilosis complex; however, a quality-controlled database must be available to provide an accurate analysis (29). In all methods described above, only limited numbers of C. metapsilosis isolates (1, 6, and 2, respectively) were tested by the authors (11,17,29). In our analysis, we were able to validate our strategy by testing 50 strains of C. parapsilosis (sensu stricto), 40 strains of C. orthopsilosis, and 10 strains of C. metapsilosis, including strains from 2 different countries.…”
Section: Discussionmentioning
confidence: 99%